(3GdJWQb HGdWH Edi GdSYGOIs - (3Ydj Hf QVhGf Hf Ydj Hf LYaQ GdeUQj, CHj GdMSf,J (B453 (3g` s
(3ChdgG (B:s
(3bGd GHf QVhGf (B: (3bO HjfG ai cJHfG Cf CHbQGW GSJYed JYdje UfGYI GdWH , hCf LGdjfhS gPH JYdje CHbQGW s
(3BNQgG (B:s
(3hUQa HGbi jheg ai GdYed GdUGdM hGdacQ ai edchJ GdSehGJ hGdCQV , hYHO Gddg hCWGY GdYbd , Pdc eG CQOfG HjGfg s
(3fSNI GSJNQLgG fGSNgG ef fSNI ObjbI GdNW cKjQI GdNWCs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B51 s
(3eUOQ GbJfGA GdCUd (B:s
(3Mcje ChZdhG Ydi HGTG (B(691(3)) s
Keywords: (3GdWHs